2008
DOI: 10.1287/mksc.1080.0398
|View full text |Cite
|
Sign up to set email alerts
|

Supermarket Pricing Strategies

Abstract: Most supermarket firms choose to position themselves by offering either everyday low prices (EDLP) across several items or offering temporary price reductions (promotions) on a limited range of items. While this choice has been addressed from a theoretical perspective in both the marketing and economic literature, relatively little is known about how these decisions are made in practice, especially within a competitive environment. This paper exploits a unique store level data set consisting of every supermark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
154
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(170 citation statements)
references
References 33 publications
9
154
1
6
Order By: Relevance
“…The importance of unobserved heterogeneity and correlated unobservables is not unique to this setting, arising as well in the contexts of peer e¤ects, locational sorting, and entry games (e.g. Bajari et al (2010), Bayer andTimmins (2007), Ellickson and Misra (2008)). Following this literature, I proceed by identifying a suitable instrument for competitor's size.…”
Section: The Nature Of Local Conductmentioning
confidence: 99%
“…The importance of unobserved heterogeneity and correlated unobservables is not unique to this setting, arising as well in the contexts of peer e¤ects, locational sorting, and entry games (e.g. Bajari et al (2010), Bayer andTimmins (2007), Ellickson and Misra (2008)). Following this literature, I proceed by identifying a suitable instrument for competitor's size.…”
Section: The Nature Of Local Conductmentioning
confidence: 99%
“…While this makes e¢ cient use of the often limited data at hand, it can severely limit the usefulness of the model for performing informative counterfactuals or identifying the deep parameters that drive these strategic interactions. For example, in their study of supermarket pricing behavior, Ellickson and Misra (2008) found strong evidence that supermarket chains favor strategies that accord with their rivals, but were unable to pin down exactly why such assortative matching was in fact bene…cial to the …rms. The goal of this paper is to provide a method for incorporating additional, post-choice outcome data into structural models of static discrete games that will allow the researcher to obtain more nuanced insights into a …rm's decision making and the nature of strategic interactions across …rms.…”
Section: Introductionmentioning
confidence: 99%
“…1 We illustrate our estimation technique with an empirical exercise that builds on an earlier analysis of supermarket pricing strategies. In a recent paper, Ellickson and Misra (2008) treat a supermarket's pricing decision as a discrete, store level game between rival chains and estimate the parameters of a reduced form pro…t function using techniques developed in Bajari et al (2010). While they …nd strong evidence of assortative matching by strategy (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…They found that although chains and stores employed EDLP and HiLo as signalling strategies, retailers actually practiced as many as five different pricing strategies at the brand level (see Table 1). Bolton et al, 2010;Bolton and Shankar, 2003 An array of research demonstrates that retailers, while perceived as fitting into neat strategy boxes, often realise very different strategies at the store shelf-edge (Ellickson and Misra, 2008;Gauri et al, 2008;Shankar and Bolton, 2004). Whether this is deliberate or accidental is not entirely clear, due in part to most retailers' sensitivity to revealing their pricing practices.…”
Section: Grocery Pricing Strategiesmentioning
confidence: 99%
“…While popular debate considers the possibilities of variable grocery prices (New York Times, 2012) and the potential for 'customized pricing' (Bolton et al, 2010), the published research evidence suggests that UK and US grocery practices suffer from a more fundamental lack of alignment between business strategy and pricing execution (Ellickson and Misra, 2008). The role of local pricing has seemingly diminished as head office based pricing executives introduce a degree of price rigidity and pricing rules.…”
Section: Grocery Pricing Practicesmentioning
confidence: 99%